2019
DOI: 10.1016/j.enconman.2018.12.080
|View full text |Cite
|
Sign up to set email alerts
|

How to decarbonise international shipping: Options for fuels, technologies and policies

Abstract: (a, b,*) , James Brierley (c) , Chester Lewis (d) , Line Skatvedt (c) , Jamie Speirs (a, e) , Adam Hawkes (a, b) , Iain Staffell (c)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
234
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 467 publications
(321 citation statements)
references
References 81 publications
4
234
0
1
Order By: Relevance
“…A general overview of the measures with high CO 2 reduction potential can be found in Reference [13], while a specific focus on emission reduction in the port area is in Reference [14]. A holistic assessment of the combined potential of fuels, technologies and policies to reduce GHG emissions from international shipping can be found in Reference [15]. Several quite recent special issues dealing with specific aspects of sustainability in the shipping and port industry are also available [16][17][18][19], further confirming the strong interest in the topic.…”
Section: Introductionmentioning
confidence: 99%
“…A general overview of the measures with high CO 2 reduction potential can be found in Reference [13], while a specific focus on emission reduction in the port area is in Reference [14]. A holistic assessment of the combined potential of fuels, technologies and policies to reduce GHG emissions from international shipping can be found in Reference [15]. Several quite recent special issues dealing with specific aspects of sustainability in the shipping and port industry are also available [16][17][18][19], further confirming the strong interest in the topic.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is suggested that the authorities support technological innovations such as the "design efficiency" of newly built vessels to improve the energy efficiency. Ultimately, there is no silver bullet solution to decarbonization [37]. The route to decarbonizing shipping requires a combination of various mitigation policies, which is a long-term process.…”
Section: Discussionmentioning
confidence: 99%
“…[4] proposed a policy analysis, which revisited the progress of technical, operational, and market-based routes and their associated controversies. Balcombe et al [37] reviewed the potential of multiple pathways for shipping decarbonization, including energy efficiency technologies, alternative fuels, and policies. They suggested that a combination of pathways is required.…”
Section: A Brief Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Global climate changes that include global warming and other harmful effects of human activity led to the introduction of strict environmental requirements for automobiles. This measure, accompanied by a rise in oil prices, contributed to the beginning of the search for alternative modes of transport, including the use of innovative technologies and smart grids (Balcombe et al 2019).…”
Section: Electric Vehicles and Ioementioning
confidence: 99%